Pengaruh Kebijakan Dividen dan Risiko Bisnis terhadap Struktur Modal pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia pada Periode 2015–2019 - Hasan, Putri Juliyanti (Universitas Nahdlatul Ulama Surabaya, 2023)
The research aims to determine and analyze the effect of dividend policy and business risk on capital structure in property and real estate companies. The sampling technique used is purposive sampling. The population in this research amounted to 65 companies and based on the sampling technique in the annual financial statements of property and real estate companies for the 20152019 period there were 15 samples or 75 observed data. The analysis used in this research is Multiple Linear Regression Analysis. The results of this research indicate that the dividend policy has a positive and significant effect on capital structure and business risk has no effect on capital structure.